2020
DOI: 10.1039/c9gc04341a
|View full text |Cite
|
Sign up to set email alerts
|

Understanding laccase/HBT-catalyzed grass delignification at the molecular level

Abstract: An in-depth study on the pathways underlying wheat straw and corn stover delignification by a laccase/HBT system. New insights were obtained by comprehensive fractionation, purification and analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 65 publications
(95 reference statements)
5
36
0
Order By: Relevance
“…Interestingly, diketone products, pyrolysis markers for dihydroxyphenylketones, had increased significantly after fungal growth from 0.16 ± 0.00% to 0.25 ± 0.00% of the relative abundance of lignin-derived pyrolysis products; and consequently explained a major part of the increase of the C α -oxidized substructures. These markers have also been observed after the action of the white-rot fungus Ceriporiopsis subvermispora [19] and for laccase-mediator systems [27], suggesting that O-4′-cleavage of β-O-4′ aryl ethers is likely one of the involved ligninolysis routes. anserina on wheat straw lignin isolate and insoluble wheat glucoronoarabinoxylan.…”
Section: Structural Characterization Of Lignin After Growth Of P Ansmentioning
confidence: 78%
“…Interestingly, diketone products, pyrolysis markers for dihydroxyphenylketones, had increased significantly after fungal growth from 0.16 ± 0.00% to 0.25 ± 0.00% of the relative abundance of lignin-derived pyrolysis products; and consequently explained a major part of the increase of the C α -oxidized substructures. These markers have also been observed after the action of the white-rot fungus Ceriporiopsis subvermispora [19] and for laccase-mediator systems [27], suggesting that O-4′-cleavage of β-O-4′ aryl ethers is likely one of the involved ligninolysis routes. anserina on wheat straw lignin isolate and insoluble wheat glucoronoarabinoxylan.…”
Section: Structural Characterization Of Lignin After Growth Of P Ansmentioning
confidence: 78%
“…While many of the reports focus strictly their attention on the cytotoxicity and biocompatibility studies, the biodegradability of these materials remains largely unexplored. It is well known that lignin can be partially decomposed by enzymes, 16,184 but most of these smart materials described above are based on chemical modification of lignin, which probably disrupts the degradability process. For instance, cross-linked lignin materials are likely drastically less biodegradable and the absence of phenolic hydroxyl groups hinders accessibility of these primary sites in enzymatic degradation processes.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…2.9 incubated with steamexploded biomass (Eucalyptus globulus) at 60 °C for 24 h in the presence of HBT as mediator obtaining a decrease in the intensity of the IR bands associated with lignin aromatic backbone and lignin−hemicellulose linkages. 152 A very recent study sheds light on the intimate mechanism of straw delignification by a LC/HBT mediator system: 153 subtle analytical methods revealed Cα oxidation and Cα−Cβ and β-O−4 oxidative cleavage. In the same study, a significant reduction in phenylcoumaran and resinol linkages was found, showing that also the poorly reactive β−β and β−5 C−C links could be targets of the laccase/mediator system.…”
Section: Protocolsmentioning
confidence: 99%